2013
DOI: 10.1016/j.actamat.2013.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of enthalpy and entropy on the phase stability of equiatomic high-entropy alloys

Abstract: High configurational entropies have been hypothesized to stabilize solid solutions in equiatomic, multi-element alloys which have attracted much attention recently as "high-entropy" alloys with potentially interesting properties. To evaluate the usefulness of configurational entropy as a predictor of single-phase (solid solution) stability, we prepared five new equiatomic, quinary alloys by replacing individual elements one at a time in a CoCrFeMnNi alloy that was previously shown to be single-phase [1]. An im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
500
2
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,114 publications
(560 citation statements)
references
References 18 publications
15
500
2
7
Order By: Relevance
“…Similar phenomena have also been observed in other high-temperature annealing experiments. [15][16][17] The second myth is that only simple solid solution phases (BCC/FCC) are the desired phases for practical applications of HEAs. This is also not true.…”
Section: High-entropy Effectmentioning
confidence: 99%
“…Similar phenomena have also been observed in other high-temperature annealing experiments. [15][16][17] The second myth is that only simple solid solution phases (BCC/FCC) are the desired phases for practical applications of HEAs. This is also not true.…”
Section: High-entropy Effectmentioning
confidence: 99%
“…If every lattice site were to be occupied with equal probability by each of the four elements, a configurational entropy of k B ln 4 ∼ 1.2 × 10 −4 eV/K would result. However, atomic size, enthalpy of mixing and additional considerations surely affect stability also [3][4][5][6][7]. Indeed, decomposition into multiple phases has been observed experimentally in certain high entropy alloy families [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Otto et al recently published a systematic investigation on the effect of entropy on phase stability of HEAs. [4] The authors demonstrated that high configurational entropy is not the only sufficient criterion to predict whether an equiatomic multi-component alloy will form as a single-phase solid solution. In their study, they found only NiFeCrCoMn to be a single-phase fcc solid solution and HEA.…”
mentioning
confidence: 99%
“…This led the system to act less like an ideal solution and resulted in the formation of a multi-phase alloy with a reduced overall entropy. [4] There has also been interest in finding descriptors to predict the likely crystallographic lattice (fcc or bcc) that the solid solution will form upon. One descriptor that has been reasonably successful in predicting the lattice structure is the average valence concentration (or average periodic table group number) (VEC).…”
mentioning
confidence: 99%